ZADANIE W ZAŁĄCZNIKU
![ZADANIE W ZAŁĄCZNIKU class=](https://pl-static.z-dn.net/files/ded/f29e743d6a59dd2a1feaf2832882cb4e.png)
Cześć!
Obliczenia
[tex]1-4(x^2-x+2)(1+x^2)=1-4(x^2+x^4-x-x^3+2+2x^2)=\\\\=1-4(x^4-x^3+3x^2-x+2)=1-4x^4+4x^3-12x^2+4x-8=\\\\=\boxed{-4x^4+4x^3-12x^2+4x-7}[/tex]
Odpowiedź:
1 - 4 ([tex]x^{2} +x^{4} -x - x^{3} +2 +2x^{2}[/tex]) =1 - 4 ([tex]x^{4} - x^{3} + 3x^{2} - x +2 ) =[/tex] [tex]1 - 4x^{4} +4x^{3} -12x^{2} +4x -8 = - 4x^{4} +4x^{3} -12x^{2} +4x -7[/tex]
Szczegółowe wyjaśnienie: